'Luminescent carbon nanodots: Current prospects on synthesis, properties and sensing applications'. (11th January 2021) - Kottam, Nagaraju; S P, Smrithi
Abstract: 'Nanocarbon science' ignited interest owing to its substantial scope in biomedicine, energy and environment-beneficial applications. Carbon dots (C-dots), a multi-faceted nanocarbon material, emerged as a homologue to graphene and henceforth geared extensive investigation both on its properties and applications. Eximious properties like excitation-wavelength tunable fluorescence emission, up-converted photoluminescence, photon-induced electron transfer, low cytotoxicity, chiroptical behavior, high chemical and photostability set the ground for astounding applications of carbon dots. Abundant availability of raw 'green' precursors complementary to other molecular/graphitic precursors make them environmentally benign, inexpensive and ultimately 'nanomaterials of the current decade'. This review focuses on the synthesis of carbon dots not only from natural sources but also from other carbonaceous precursors and contemplates the inherent but controversial properties. We also aim to garner the attention of readers to the recent progress achieved by C-dots in one of its prestantious area of applications as nanosensors.